Problem-Solving Skills and Productive Struggle of Students in Solving Mathematical Problems in Elementary School - Mufliva, Rosiana; Turmudi, Turmudi; Herman, Tatang; Iriawan, Sandi Budi; Fitriani, Andhin Dyas (SEAMEO Regional Centre for QITEP in Mathematics, 2024)
The research is motivated by the need to gain a deeper understanding of students’ mathematical problem-solving abilities, particularly in algebra, and to identify and address the productive struggles the encounter while solving problems. This research aims to analyze students' mathematical problem-solving abilities in solving algebra problems and identify students' productive struggles in solving these problems. This research was carried out using a qualitative approach with descriptive methods and instruments used in this research are problem solving ability tests, questionnaires that have been validated by education experts, and interview guides. Researchers selected students based on their level of productive struggle, namely high, medium, and low. The result revealed that students who have high productive struggle can answer the three questions correctly according to the problem-solving stages, starting from the understanding stage, transformation stage, process skills stage, and conclusion stage. Students who have moderate productive fighting power can answer the three questions only up to the understanding and transformation stage. At the process skills stage, students show errors in calculating and need teacher motivation to continue their struggle in solving mathematical problems. Students who have low productive fighting power can answer questions only up to the understanding stage, limited to writing back what they know and ask. In this category, students need intervention assistance from researchers to encourage their productive struggles. This assistance does not eliminate students' opportunities to think actively, on the contrary, through this method students are required to interpret their knowledge.